Hawks Nest - Crandall, William, 1956- (SAGE knowledge. Cases., 2016)
This case looks at serious safety violations in the workplace, focussing on the example of a tunnel built by the engineering company Rinehart and Dennis in West Virginia. By cutting safety costs they saved money at the expense of their worker's lives and health.